Cognitive engagement and online political participation on social media among youths in Malaysia: the moderating role of political knowledge - Abdulrauf, Aishat Adebisi (EDP Sciences., 2017)
User-Generated Contents is a type of brand-related communications on social media platforms. User-Generated Contents (UGC) offers consumers the opportunity of sharing their experiences, contribute their opinion and communicate with other.This implies that brand managers no longer have solitary control in managing the brand images of their brands.Therefore, this study set out to examine the effect of user-generated contents on hedonic brand image and functional brand.Also, the study determines how hedonic and functional brand image influence brand purchase intention. 114 followers of fan pages of Malaysian automotive brands were surveyed. The hypotheses formulated were tested using PLS-SEM. The findings revealed that, UGC have significant and positive impact on both functional and hedonic brand image.Furthermore, functional and hedonic brand image have significant impact on purchase intention. This study provides insight on the importance of UGC, functional and hedonic brand image to brand managers.